Optimizing the Application of Online Systems in Correspondence Management at the Faculty of Education, Universitas Negeri Makassar - Muh. Darwis; M. Awaluddin; Annisa Salsabila Arief; Herlina Sakawati (Pinisi Journal of Education and Management, 2022)
This study aims to describe the optimization of the application of the online system in the management of correspondence at the Faculty of Education, Universitas Negeri Makassar. This research is a qualitative descriptive study. The techniques used in data collection are observation, interviews, and documentation. The data analysis presented in this study is: data condensation, presenting data and drawing conclusions or verification. The results of the study indicate that the optimization of the application of the online system in the management of correspondence at the Faculty of Education, Universitas Negeri Makassar is classified as less than optimal based on the following aspects: security which is considered poor has not been proven to be 100% secure; Speed and accuracy are said to be poor looking depending on the internet connection; The accountability of the Gmail spreadsheet letter numbering is said to be poor, seen by employees who are less able to maintain the confidentiality of the letter numbering; the linkage of the letter numbering is said to be good seen from the employees in the two sub-sections who can use it well; the standardization of letter numbering is said to be poor seen from employees who are not careful enough to pay attention to the filling column; Effective and efficient is said to be not good, judging from its use it has not run effectively and efficiently.